2004
DOI: 10.1073/pnas.0401670101
|View full text |Cite
|
Sign up to set email alerts
|

Estimating metazoan divergence times with a molecular clock

Abstract: Accurately dating when the first bilaterally symmetrical animals arose is crucial to our understanding of early animal evolution. The earliest unequivocally bilaterian fossils are Ϸ555 million years old. In contrast, molecular-clock analyses calibrated by using the fossil record of vertebrates estimate that vertebrates split from dipterans (Drosophila) Ϸ900 million years ago (Ma). Nonetheless, comparative genomic analyses suggest that a significant rate difference exists between vertebrates and dipterans, beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
285
1
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 427 publications
(299 citation statements)
references
References 52 publications
(40 reference statements)
11
285
1
2
Order By: Relevance
“…Hox: facts and guesses J Garcia-Fernàndez peared. However, it was soon found that dipoblast Cnidarians already possessed Hox and ParaHox genes (Finnerty and Martindale, 1999) The four-gene model is supported by phylogenetic analyses of the 60 aa homeodomain alone (or the homeodomain plus five flanking aa), of proteins that diverged more than 800 million years ago (Banerjee-Basu and Baxevanis, 2001; Peterson et al, 2004). The bootstrap values for any particular grouping of Hox vs ParaHox genes range from 40 to 70% (Brooke et al, 1998;Finnerty and Martindale, 1999;Banerjee-Basu and Baxevanis, 2001;Minguillón and Garcia-Fernàndez, 2003).…”
Section: Introductionmentioning
confidence: 89%
“…Hox: facts and guesses J Garcia-Fernàndez peared. However, it was soon found that dipoblast Cnidarians already possessed Hox and ParaHox genes (Finnerty and Martindale, 1999) The four-gene model is supported by phylogenetic analyses of the 60 aa homeodomain alone (or the homeodomain plus five flanking aa), of proteins that diverged more than 800 million years ago (Banerjee-Basu and Baxevanis, 2001; Peterson et al, 2004). The bootstrap values for any particular grouping of Hox vs ParaHox genes range from 40 to 70% (Brooke et al, 1998;Finnerty and Martindale, 1999;Banerjee-Basu and Baxevanis, 2001;Minguillón and Garcia-Fernàndez, 2003).…”
Section: Introductionmentioning
confidence: 89%
“…The chosen root prior is based on the observed presence of both ecdysozoans and lophotrochozoans (protostomes) at the base of the Cambrian indicating an older divergence (earlier than 542 Ma) of this group. Previous molecular clock studies also recovered a divergence of the protostomes at this time [33,42]. The analyses were run initially under the prior in order to confirm that the distribution of ages was sufficiently uninformative for posterior sampling.…”
Section: (A) Molecular Sequencesmentioning
confidence: 99%
“…Molecular analyses so far have not been able to confirm either of the morphological hypotheses. In order to assess the relative merits of the different morphological hypotheses for the position of aplacophorans, we sequenced seven nuclear housekeeping gene mRNAs [33] from all major classes of molluscs (except monoplacophorans). These data were combined with a representative set of lophotrochozoan and ecdysozoan taxa as outgroups and analysed in a Bayesian phylogenetic framework.…”
Section: Introductionmentioning
confidence: 99%
“…Early application of a Bayesian relaxed clock method to the problem of metazoan divergence times by Aris-Brosou & Yang (2003) found phylum-level splits in the Deuterostomia at ca 520-530 Myr ago, matching Peterson et al's (2004) results. However, they used an unrealistic model of molecular evolution in their analysis (Ho et al 2005) and other analyses that apply potentially more appropriate models (Douzery et al 2004) have continued to find somewhat deeper divergence dates for the Bilateria.…”
Section: When Did Deuterostome Groups Originate?mentioning
confidence: 75%